Structure of co-authorship network in UPM journal publications database from 2007-2010 - Ismail, Zurita (2018)
Co-authorship is one of the most tangible forms of research collaboration. A co-authorship network is a social network in which the authors through participation in one or more joint publications are linked (undirectedly) to each other. The present work used social network analysis to study co-authorship network of UPM journal publications database for the ﬁrst four years of Research University (2007-2010) with the aid of Mathematica 11.